PENGARUH PROSEDUR PELAYANAN DAN KEMAMPUAN PEGAWAI TERHADAP KUALITAS PELAYANAN PEMBUATAN PASPOR DI KANTOR IMIGRASI KELAS I SEMARANG - Jeremy Woosnam; Tri Yuniningsih (Journal of Public Policy and Management Review, 2018)
The implementation of public services can’t be separated from the relation of government as the services providers and the public as the users of public services provided by the government. Semarang Class I Immigration Office is the agencies in the field of immigration services. One of the services provided by Semarang Class I Immigration Office is the making of passport for people who need it. The passport making service quality is influenced by several variables, such as service procedures and employee’s ability. This research aims to determine the influence of service procedures and the ability of employees towards the service quality of passport making in Semarang Class I Immigration Office. The approach that used in this research is a quantitative approach by conducting research on 100 respondents who want to apply passport. The result of the research on the respondents will be analyzed using Kendall correlation coefficient, Kendall concordance coefficient, and determination coefficient. The result showed that there is a positive and significant correlation between service procedures and employee’s ability with the service quality. The percentage of influence between service procedures to service quality is 9,79%. While the percentage of influence between employee’s ability to service quality is 21,52%. The value of determination coefficient in collaboration of service procedures and employee’s ability is 69,88%. It can be concluded that there is a significant influence between service procedures and employee’s ability towards the service quality of passport making in Semarang Class I Immigration Office.